MENUMBUHKAN JIWA DARI SEJAK SMA SISWA MUHAMMADIYAH 2 JAKARTA - Ahmad Faishal; Muhammad Rayhan Afif; Fahreza Ifankha; Nabil Rasya Ramadhan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Community Service Activities (PKM) were conducted by a team from the Faculty of Economics and Business, Universitas Muhammadiyah Prof. Dr. HAMKA, on Wednesday, June 17, 2026, at SMA Muhammadiyah 2 Jakarta, located on Jl. Garuda No. 33, Kemayoran, Central Jakarta. This activity, titled “Building an Entrepreneurial Spirit since High School,” aimed to introduce students to the basic concepts of entrepreneurship and encourage them to build an entrepreneurial mindset as early as possible. A baseline assessment gathered from 120 students showed that 54.2% had never engaged in any entrepreneurial activity at all, reflecting a low level of practical experience despite most students already being at the senior-high level. This condition was compounded by a school policy prohibiting students from selling goods on school grounds, which closed off the practice space most accessible to them. The methods used included lectures, interactive discussion, a question-and-answer session, sharing of success stories from young entrepreneurs, and a simple business-idea exercise. Pre-test results indicated a fairly good baseline understanding, with 93.57% correct responses, while the post-test used an essay format so students could express their understanding more fully. The evaluation showed a marked shift in students’ perception of entrepreneurship, supported by family, peer, and teacher influence as well as constrained by low self-confidence, limited motivation, and fear of failure. The expected outcome of this activity is an increase in students’ awareness, creativity, and courage to take the first step toward becoming young entrepreneurs, grounded in honesty and integrity as exemplified by the Prophet Muhammad SAW as a trader.